New insights into the pathogenesis and therapeutics of episodic ataxia type 1 - D’Adamo, Maria Cristina; Hasan, Sonia; Guglielmi, Luca; Servettini, Ilenio; Cenciarini, Marta; Catacuzzeno, Luigi; Franciolini, Fabio (Frontiers in Cellular Neuroscience, 2015)
Episodic ataxia type 1 (EA1) is a K+ channelopathy characterized by a broad spectrum of symptoms. Generally, patients may experience constant myokymia and dramatic episodes of spastic contractions of the skeletal muscles of the head, arms, and legs with loss of both motor coordination and balance. During attacks additional symptoms may be reported such as vertigo, blurred vision, diplopia, nausea, headache, diaphoresis, clumsiness, stiffening of the body, dysarthric speech, and difficulty in breathing. These episodes may be precipitated by anxiety, emotional stress, fatigue, startle response or sudden postural changes. Epilepsy is overrepresented in EA1. The disease is inherited in an autosomal dominant manner, and genetic analysis of several families has led to the discovery of a number of point mutations in the voltage-dependent K+ channel gene KCNA1 (Kv1.1), on chromosome 12p13. To date KCNA1 is the only gene known to be associated with EA1. Functional studies have shown that these mutations impair Kv1.1 channel function with variable effects on channel assembly, trafficking and biophysics. Despite the solid evidence obtained on the molecular mechanisms underlying EA1, how these cause dysfunctions within the central and peripheral nervous systems circuitries remains elusive. This review summarizes the main breakthrough findings in EA1, discusses the neurophysiological mechanisms underlying the disease, current therapies, future challenges and opens a window onto the role of Kv1.1 channels in CNS and PNS functions.